Economic Factors Affecting Business Income from Potato Plants (Solanum tuberosum. L) - Novrini, Susan; Riyadh, Mhd. Ilham; Pratiwi, Henny (PT Inovasi Pratama Internasional, 2024)
Indonesia is an agrarian (agricultural) country where agriculture plays an important role in the national economy. One of the farming businesses that is currently developing is potato cultivation, especially in Mardingding Village, Pematang Silimahuta District, Simalungun Regency. In running and increasing farm production there are three important factors, namely: land area, labor, and capital. However, sometimes the level of agricultural production is influenced by factors beyond the ability of farmers, one of which is natural factors, therefore there is a need for research to help and research is needed to help and analyze what factors affect farming results, especially in plants. potato. In this study, it is explained how the influence of the determinants of potato crop yields, especially in Mardingding Village, Pematang Silimahuta District, Simalungun Regency.